Guardia Nacional, ciudadanía y poder en Tucumán, Argentina (1850-1880). - Macías, Flavia Julieta (Revista Complutense de Historia de América, 2001)
This article examines the process of construction of the citizenship and the national identity in Argentina between 1850-1880, since a military perspective. The work focuses on the National Guard, the military institution created by the national state as a strategy to promote the civic duties and the national army service. Provincial case shows the local tensions and conflicts link to the army citizenship process of construction and to the creation of a national identity.